Development of Inventors’ Activities in Latvia: Inventors’ Societies, Exhibitions, Patents and the Rationalizers’ Movement - Griņevičs, Ivans (History of Engineering Sciences and Institutions of Higher Education, 2020)
The article introduces inventors’ activities and inventors’ societies in Latvia in the 18th century, when it was part of tsarist Russia, until 2019. There is only one study on inventors’ activities, which includes the interwar period. There are many engineers among inventors, and this study reflects the participation of students, graduates and lecturers of Riga Polytechnicum (RP), Riga Polytechnic Institute (RPI) and Riga Technical University (RTU) in inventors’ activities. The research provides an insight into the history of protection of inventions, inventors’ activities, international exhibitions of inventions and innovations, activities of inventors’ societies.